Effect of Electronic Surveillance on Task Performance: Mediating Role of Digital Transformation Moderating Role of Perceived Organizational Support - Kamran Khan; Mahvia Gul; Husnain Ali Chaudhry (Journal of Information and Organizational Sciences)
Purpose: Digital transformation is of increasing relevance for both practitioners and scholars. Modern digital technologies, services, and systems are extremely important for social development because they are currently taking place in the economy, production, and society as a whole. This study delves into the crucial domain of electronic surveillance within the healthcare sector, assessing its influence on employee task performance. It investigates the interplay between electronic surveillance, perceived organizational support, and digital transformation. Our research aims to unravel how perceived organizational support moderates the relationship between electronic surveillance and task performance while also examining the mediating role of digital transformation in this dynamic.